Study of the Effect of Regulating Alloying Elements and Optimizing Heat Treatment Processes on the Microstructure Properties of 20MnCr5 Steel Gears - Li Luo; Yong Chen; Fucheng Zhao; Weifeng Hua; Xu Song; Zhengyun Xu; Zhicheng Jia (Lubricants)
To optimize heat treatment of gears for high-end equipment and enhance their fatigue resistance, this paper studied the effects of Al, Mn and Cr content on surface microstructure, i.e., martensite, retained austenite, grain size, hardened layer depth and residual stress under different carburizing temperatures and low tempering of 20MnCr5 steel FZG gear. With numerical simulation combined with experimental verification, this paper establishes a simulation model for the carburizing process of 20MnCr5 steel FZG gear, analyzing the microstructure and retained austenite volume of the gear surface, after carburizing and quenching, by a scanning electronic microscope (SEM) and X-ray diffraction (XRD). In addition, the paper reveals the influence of the optimized heat treatment on the residual stress of the gear regulated with Al, Mn and Cr content in the meshing wear range of 200~280 µm. This study provides a guiding model theory and experimental verification for regulating proportions of alloying elements and optimizing the heat treatment process of low-carbon-alloy steel.